2014
DOI: 10.3389/fendo.2014.00112
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Physical Activity Predicts Hip and Spine Bone Mineral Content in Children and Adolescents Ages 5–15 Years: Iowa Bone Development Study

Abstract: This study examined the association between physical activity (PA) and bone mineral content (BMC; gram) from middle childhood to middle adolescence and compared the impact of vigorous-intensity PA (VPA) over moderate- to vigorous-intensity PA (MVPA). Participants from the Iowa bone development study were examined at ages 5, 8, 11, 13, and 15 years (n = 369, 449, 452, 410, and 307, respectively). MVPA and VPA (minutes per day) were measured using ActiGraph accelerometers. Anthropometry was used to measure body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 35 publications
3
38
2
Order By: Relevance
“…Total PA explained 1%-2% of the variability in BMC (Janz et al 2006) Children who maintained high levels of PA over the 3-y period (≥50th percentile) accrued, on average, 14% more trochanteric BMC and 5% more whole-body BMC relative to peers maintaining low levels of PA (<50th percentile) (Janz et al 2006) 1 study found that spending a higher proportion of total PA in MPA-VPA relative to LPA was favourably associated with BMC, BMD, and bone area (Heidemann et al 2013 (1/1 studies; Tobias et al 2007); Hip BMC: favourable associations (2/2 studies; Janz et al 2001Janz et al , 2014a; Spine BMC: associations were favourable (2/3 studies; Janz et al 2001 and …”
Section: No Serious Imprecisionmentioning
confidence: 99%
See 4 more Smart Citations
“…Total PA explained 1%-2% of the variability in BMC (Janz et al 2006) Children who maintained high levels of PA over the 3-y period (≥50th percentile) accrued, on average, 14% more trochanteric BMC and 5% more whole-body BMC relative to peers maintaining low levels of PA (<50th percentile) (Janz et al 2006) 1 study found that spending a higher proportion of total PA in MPA-VPA relative to LPA was favourably associated with BMC, BMD, and bone area (Heidemann et al 2013 (1/1 studies; Tobias et al 2007); Hip BMC: favourable associations (2/2 studies; Janz et al 2001Janz et al , 2014a; Spine BMC: associations were favourable (2/3 studies; Janz et al 2001 and …”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…d Includes 7 longitudinal studies (Janz et al 2006(Janz et al , 2007(Janz et al , 2010(Janz et al , 2014a(Janz et al , 2014bHeidemann et al 2013;Francis et al 2014) from 2 unique samples. Six studies reported data from the Iowa Bone Development Study (Janz et al 2006(Janz et al , 2007(Janz et al , 2010(Janz et al , 2014a(Janz et al , 2014bFrancis et al 2014) and 1 study reported data from the CHAMPS study sample (Heidemann et al 2013). Results are reported separately and participants are only counted once.…”
Section: Other (Impact Measured By G-band)mentioning
confidence: 99%
See 3 more Smart Citations